Induction Chemotherapy Followed by Primary Tumor Resection Did Not Bring Survival Benefits in Colon Cancer Patients With Asymptomatic Primary Lesion and Synchronous Unresectable Metastases - Huang, Mingzhu; Yang, Ya’nan; Li, Qingguo; Wang, Chenchen; Liang, Lei; Zhu, Xiaodong; Zhang, Wen; Chen, Zhiyu; Huang, Dan; Li, Wenhua; Zhang, Xiaowei; Zhao, Xiaoying; et al. (Frontiers in Oncology, 2022)
Background It is still controversial whether primary tumor resection (PTR) improves survival in colorectal cancer (CRC) patients with unresectable metastases. Methods Colon cancer patients were enrolled and randomly allocated to with or without PTR after induction chemotherapy with XELOX or mFOLFOX6, and those with chemotherapy failure were excluded. The primary endpoint was TTF (time to strategy failure) on an intent-to-treat basis. This study is registered with ClinicalTrials.gov, number NCT02291744. Results Between April 2015 and July 2020, 140 patients were enrolled, and 54 patients were excluded due to colon obstruction (16), perforation (1), disease progression (22), death (1), radical resection (3), or other reasons (11). After induction chemotherapy, 86 patients were randomized into group A (the resection group, n = 42) or group B (chemotherapy-alone group, n = 44). The median TTF was 143 days (95% CI: 104.9–181.1) in group A and 196 days (95% CI: 96.5–295.5) in group B (HR: 0.930 95% CI: 0.589–1.468, p = 0.755), and there was no significant difference in PFS, OS, and incidence of chemotherapy-related adverse events between two groups. The primary lesion-related events after PTR in group A were significantly fewer than those in group B. Patients with a tumor regression grade (TRG) score of 2 had longer TTF and PFS than those with score of 3. Conclusion PTR after induction chemotherapy could not bring survival benefits for colon cancer patients with unresectable metastases, and it is not recommended routinely. However, it also requires individualized treatment as colon obstruction or perforation occurred in some patients and PTR could reduce primary tumor-related events, and the TRG score might help for selection of beneficial patients.